Properties of channels reconstituted from the major intrinsic protein of lens fiber membranes (The Rockefeller University Press, 1990)
Detergent-solubilized plasma membrane protein of either adult bovine or calf lens and high-performance liquid chromatography-purified major intrinsic protein (MIP) of the lens were reconstituted into unilamellar vesicles and planar lipid bilayers. Freeze-fracture studies showed that the density of intramembrane particles in the vesicles was proportional to the protein/lipid ratio. At high ratios, these particles crystallized into tetragonal arrays as does MIP in lens fibers. Channels induced by either purified MIP or detergent-solubilized protein had essentially identical properties. The conductance of multichannel membranes was maximal near 0 mV and decreased to 0.49 +/- 0.08 of the maximum value at voltages greater than 80 mV. The dependence of the conductance on voltage was well fit by a two-state Boltzmann distribution. Voltage steps greater than 30 mV elicited an ohmic current step followed by a slow (seconds) biexponential decrease. The amplitudes and time constants depended on the magnitude but not the sign of the voltage. Steps from 100 mV to voltages less than 30 mV caused the channels to open exponentially with a millisecond time constant. Analysis of latency to first closure after a voltage step gave nearly the same time constants as multichannel kinetics. Single- channel conductance is proportional to salt concentration from 0.1 to 1.0 M in KCl. In 0.1M KCl, the channel had two preferred conductance states with amplitudes of 380 and 160 pS, as well as three additional substates. Multi- and single-channel data suggest that the channel has two kinetically important open states. The channel is slightly anion selective. The properties of the channel do not vary appreciably from pH 7.4 to 5.8 or from pCa 7 to 2. We propose that a channel with these properties could contribute to maintenance of lens transparency and fluid balance.